REAL-TIME KINEMATIC GPS FOR CADASTRAL SURVEYING - Pirti, A.; Arslan, N.; Deveci, B.; Aydin, O.; Erkaya, H.; Hosbas, R. G. (TAYLOR & FRANCIS LTD, 2009)
Real-Time Kinematic surveys with the Global Positioning System (RTK GPS) have been used for a variety of different surveying applications. Its use for cadastral work is becoming commonplace. A case study was conducted to investigate the use of the RTK GPS technique for boundary surveys. For this purpose, measurements were performed it? the city of Sakarya, Turkey, on 30-31 May and I June 2006. One hundred and twenty points were selected ill both normal and difficult measurement conditions in the project area. The analyses were made in three steps. In the first step, the GPS results obtained on different days with three different reference points were compared; in the second, the total station measurement results were compared with each other; in the third, the GPS measurement results were compared with those of the total station. The results showed differences of tip to 100 millimetres between the coordinates derived from the two survey methods in the obstructed areas. We conclude that the RTK technique competes well with the traditional survey methods in terms of accuracy except it? obstructed areas. Also, the RTK method complies easily with survey standards specified by current legislation.
Keywords: RTK GPS; Cadastral surveying; Turkey; Boundary surveys; Engineering; Geology; Remote Sensing